Evaluation of the field performance and genetic diversity of 23 varieties of okra from Bangladesh using RAPD markers (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not availableBangladesh J. Plant Taxon. 27(1): 195-199, 2020 (June)